Ṭarīqah Mubāsyarah in The Learning of Arabic Speaking Skill: Study Analysis with Al-Iṭṭiṣāli Approach - Ritonga, Nur'ainun; Putra, Wahyu Hanafi; Isnaini, Rohmatun Lukluk (Institut Agama Islam Negeri Palangka Raya, 2024)
This study aims to identify the steps, advantages, and disadvantages of teaching Mahārah Kalām using the Mubāsyarah method with the Iṭṭiṣāli approach. The research employs library research with a qualitative descriptive method. Data collection involves documentation, with primary sources including an article by Baroroh et al., entitled